Mechanical properties and self-cleaning mortar capacity C/A 1: 5 of Portland cement modified with titanium dioxide (TiO2) - Flores, H. (2020)
The deterioration of the surfaces of the constructions made with mortar C/A 1: 5 of Portland cement, are produced by being exposed to the emission of toxic gases emanating from the growing automobile fleet, this problem causes alternatives to be sought in order to counteract its effect on buildings and the environment. A new method to deal this problem is the incorporation of the titanium dioxide photocatalyst (TiO2) into the Portland cement mortar, which can develop self-cleaning and air purification properties to be in contact with sunlight. This work seeks to introduce this organic component to the Portland cement mortar, used for the facade charging and structural elements, for this purpose, different percentages (5%, 7.5% and 10%) of titanium dioxide (TiO2) are added and the properties of the modified mortars making use of [1] compression tests, [2] fluidity tests, [3] absorption tests and [4] photocatalytic activity tests with which the self-cleaning capacity was verified. This study concludes that the best percentage of titanium dioxide addition is 5%, with which the Portland cement mortar is granted self-cleaning property without substantially damaging its mechanical properties.